Early stage epithelial ovarian cancer metastasis through peritoneal fluid circulation - Sigit Purbadi; Tricia Dewi Anggraeni; Angelina Vitria (BMC, 2021)
Abstract Background Although epithelial ovarian cancer (EOC) spreads through peritoneal circulation, all patients with clinical early-stage ovarian cancer (OC) benefit from routine surgical staging is still unclear. Methods This cross-sectional study used data from medical records of patients with clinical early-stage EOC who received complete surgical staging from 2006 to 2016 at our hospital. We excluded patients with non-epithelial OC or with stage IV disease. Results Among 50 patients with clinical early-stage EOC who underwent surgical staging, biopsies showed EOC cells in peritoneal fluid for 12 patients (24%), in peritoneal tissue for ten patients (20%), and omental tissue for eight patients (16%). Of those 50 patients, 40 patients had undergone peritoneal biopsies, and the other five patients also had omental biopsies. The results showed that only one (2.5%) from 40 patients with peritoneal biopsy and three (6.7%) from 45 patients with omental biopsy had no visible nodules. From cytology examination, 3 out of 26 patients (11.5%) showed positive cytology from peritoneal washing. Conclusions Routine peritoneal biopsies do not seem advantageous for patients with clinical early-stage EOC as negative visible nodules with positive biopsy results were only 1 in 40 cases. However, further study with a larger cohort is needed to obtain more information on peritoneal fluid metastasis patterns.